A Comparative Study of Feed in Tariff and Net Metering for UCSI University North Wing Campus with 100 kW Solar Photovoltaic System. (November 2016) - Tan, Rodney H.G.; Chow, T.L.
Abstract: The Feed-in Tariff (FiT) has been implemented in Malaysia since 2011 and end in 2016. Net metering will be the next renewable energy implementation mechanism. This paper presents the comparative study of FiT and Net metering for UCSI University North Wing Campus solar photovoltaic system at the economy and energy perspective. A 100kWp solar photovoltaic (PV) system model, real recorded solar radiation and university campus energy consumption data are used for this study. The 100kWp solar PV system, university campus, FiT, Net metering and CO2 avoidance computation models are developed in MATLAB/Simulink to simulate the solar PV system for FiT and Net metering cost and energy computation. The study found that the monthly energy bill cost saving for FiT and Net metering are 4.91% and 3.51% respectively. The return of investment of solar PV system implementation for FiT and Net metering are 11.5 and 16.1 years respectively. This study provides an insight cost and energy analysis for FiT and Net metering for the university campus.